To the stars! : the first American woman to walk in space - Van Vleet, Carmella; Sullivan, Kathy, 1951- (Charlesbridge, 2016)
Shares the story of renowned astronaut and distinguished scientist Kathryn Sullivan, describing how she defied the conventions of her childhood to pursue interests previously limited to boys and how she became the first woman to walk in space.